The role of religiosity in enhancing tourist loyalty through halal tourism and quality services - Martaleni Martaleni; Sugeng Mulyono; Elok Sri Utami (Innovative Marketing)
Halal tourist destinations meet the needs of Muslim travelers while also being accessible to non-Muslim visitors. This study investigates the relationship between non-Muslim visitors’ loyalty to halal products and services and the growth of halal tourism, with a focus on the role of religion as a mediating factor. Using a quantitative approach, the data were collected from 308 non-Muslim tourists in East Java Province, Indonesia, through a questionnaire. The findings reveal that perceptions of halal products and services significantly influence tourist loyalty (t-statistic = 2.789, p-value = 0.005), although the effect size is low (0.158). In contrast, perceptions of halal tourism development have a strong impact on loyalty (t-statistic = 9.225, p-value = 0.000). The study also finds that non-Muslim religiosity has a negligible effect on the relationship between halal services and loyalty, with an interaction effect value of 0.008. Overall, while higher religiosity increases the impact of halal services and tourism development on loyalty, the effects are statistically insignificant. These findings suggest that promoting halal products and services can enhance loyalty among non-Muslim tourists, which is crucial for the growth of halal tourism. Destination marketers should focus on highlighting the benefits and inclusivity of halal offerings to attract a broader audience. Furthermore, understanding the limited influence of religiosity on loyalty can help tourism providers tailor their strategies to better engage non-Muslim visitors.